2019
DOI: 10.1111/apt.15577
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of endoscopic improvement and remission according to patient‐reported outcomes in ulcerative colitis

Abstract: Background: Treatment targets for ulcerative colitis are evolving towards achievement of endoscopic improvement and remission in addition to symptom resolution. It remains to be accurately quantified what proportion of patients with symptom resolution have residual endoscopic activity that might warrant treatment modification. Aim: To quantify the prevalence of endoscopic improvement and remission amongst ulcerative colitis patients with various permutations of patient-reported outcomes. Methods: Individual pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…Because faecal calprotectin was not routinely assessed in our cohort, we were unable to evaluate its association with histologic remission. However, we expect similar findings in this cohort—the majority of patients achieving symptomatic and biochemical remission tend to achieve MES 1, and predictive value of this combination for achieving complete endoscopic remission is low 18 . Finally, and most importantly, our findings do not inform feasibility or outcomes of patients treated‐to‐target of histologic remission, but rather focuses on feasibility and outcomes of patients who achieve histologic remission in the context of conventional treat‐to‐target practices.…”
Section: Discussionmentioning
confidence: 66%
“…Because faecal calprotectin was not routinely assessed in our cohort, we were unable to evaluate its association with histologic remission. However, we expect similar findings in this cohort—the majority of patients achieving symptomatic and biochemical remission tend to achieve MES 1, and predictive value of this combination for achieving complete endoscopic remission is low 18 . Finally, and most importantly, our findings do not inform feasibility or outcomes of patients treated‐to‐target of histologic remission, but rather focuses on feasibility and outcomes of patients who achieve histologic remission in the context of conventional treat‐to‐target practices.…”
Section: Discussionmentioning
confidence: 66%
“…For patients with UC, endoscopic remission was defined as going from baseline Mayo endoscopic subscore 2 (moderate disease) or 3 (severe disease) to postinduction subscore 0 (inactive disease). Endoscopic improvement was defined as going from baseline Mayo endoscopic subscore 2 or 3 to postinduction subscore 0 or 1 25 …”
Section: Methodsmentioning
confidence: 99%
“…This suggests that continued treatment beyond 5 days might be beneficial for optimising endoscopic response rates in some patients, however, it is noted that we did not perform a day 5 flexible sigmoidsocopy in the current trial. It has been observed that over 80% of patients achieving a RBS of 0 are found to have a Mayo endoscopic sub‐score of 0‐1 with nearly 50% having a Mayo endoscopic sub‐score of 0 7 . With nearly 50% of patients achieving a RBS of 0 after 5 days of hyperbaric oxygen, it is possible that our day 5 endoscopic improvement and remission rates are quite substantial and the lower rate of day 10 endoscopic improvement in the current trial compared to the prior trial are a function of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…MES were available at study days 0 and 10, with RBS and SFS available at days 3, 5 and 10. Clinical response was assessed using the modified partial Mayo score which included the RBS and SFS specifically, given the subjectivity in the physician global assessment and the strong correlation between the RBS and MES 7 . Clinical response was defined as a reduction in the modified partial Mayo score (SFS+RBS) of 2 or more points with at least a 1 point drop in RBS.…”
Section: Methodsmentioning
confidence: 99%